1987
DOI: 10.1346/ccmn.1987.0350302
|View full text |Cite
|
Sign up to set email alerts
|

Iron Substitution in Montmorillonite, Illite, and Glauconite by 57Fe Mössbauer Spectroscopy

Abstract: Abstract--The ~TFe M6ssbauer spectra of an iron-rich montmorillonite, an illite, and two glauconites were measured and computer-fitted with appropriate Fe 3+ and Fe 2+ doublet resonances. The broad experimental Fe 3 § resonance of montmorillonite probably arises from Fe 3 § in the octahedral sites and a trans-arrangement of OH groups; however, a large variation in the neighboring environment of these sites exists. In illite this Fe 3 § resonance is similar but shows less broadening; it arises from Fe 3+ locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
5

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 17 publications
3
27
0
5
Order By: Relevance
“…This assumption was based on single crystal X-ray structure refinements by which octahedral cations in 2:1 layers of various polytypes of muscovite, paragonite and margarite were shown to occupy only cis-sites (Bailey, 1984). On the other hand, until recently it was assumed that in celadonite, glauconite and nontronite structures, both cis-and trans-octahedra can be occupied by Fe 3+ (Heller-Kallai & Rozenson, 1981;De Grave et al, 1985;Johnston & Cardile, 1987;Cardile & Brown, 1988). Drits et al (1984a) formulated structural and diffraction criteria to distinguish between dioctahedral 1M micas consisting of cis-vacant (cv 1M) or trans-vacant (tv 1M) 2:1 layers.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption was based on single crystal X-ray structure refinements by which octahedral cations in 2:1 layers of various polytypes of muscovite, paragonite and margarite were shown to occupy only cis-sites (Bailey, 1984). On the other hand, until recently it was assumed that in celadonite, glauconite and nontronite structures, both cis-and trans-octahedra can be occupied by Fe 3+ (Heller-Kallai & Rozenson, 1981;De Grave et al, 1985;Johnston & Cardile, 1987;Cardile & Brown, 1988). Drits et al (1984a) formulated structural and diffraction criteria to distinguish between dioctahedral 1M micas consisting of cis-vacant (cv 1M) or trans-vacant (tv 1M) 2:1 layers.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Until recently, the widely accepted interpretation of M6ssbauer spectra of Fe3+-rich dioctahedral 2:1 layer silicates consisted of decomposition of the corresponding spectrum into two main doublets which were assumed to be related to Fe 3+ ions in cis-and trans-octahedra of 2:1 layers (Heller-Kallai & Rozenson, 1981;Rozenson & Heller-Kallai, 1978;Govaert et al, 1978;Kotlicki et al, 1981;De Grave et al, 1985;Johnston & Cardile, 1987;Cardile & Brown, 1988). As was mentioned, the XRD data showed that trans-sites are vacant in most Fe3+-rich dioctahedral 2:1 layer silicates.…”
Section: Mossbauer Spectroscopymentioning
confidence: 99%
“…The spectrum for the untreated sample was computer-fitted with five overlapping doublets ( Figure la Johnston, 1985, 1986;Johnston and Cardile, 1987), where the 6 values are ~0.37 mm/s. The lower 6 value for the Phalaborwa vermiculite reflects a greater degree of covalency for the Fe ~+ atoms involved in this resonance.…”
Section: Untreated Vermiculitementioning
confidence: 99%
“…As mentioned above, these resonances arise from the variable environments about the trans-octahedral sites. Johnston and Cardile (1987) (2), having the larger A value, is consequently assigned to Fe 3+ in the octahedral sites which have a trans-arrangement of OH groups. As noted by Goodman and Wilson (1973), there is a preference for Ire 3+ to occupy the trans-OH octahedral site, rather than the cis-OH site.…”
Section: Untreated Vermiculitementioning
confidence: 99%
“…Many authors reduce the problem of cation distribution to the Fe distribution among cis-and trans-positions. There are many papers following this concept, so we shall mention here only the more recent ones dealing with glauconite (De Grave et al, 1985;Johnston and Cardile, 1987;Cardile and Brown, 1988).…”
Section: Introductionmentioning
confidence: 99%